President of the whole fifth grade - Winston, Sherri (New York : Little, Brown, 2010)
To gain leadership skills needed to run a cupcake-baking empire when she grows up, Brianna runs for president of the fifth grade--expecting little competition--until a new girl enters the race.
Keywords: Elections -- Fiction; Leadership -- Fiction; Baking -- Fiction; Schools -- Fiction